Improving Learning Results in Hydrocarbon Chemistry with Mind Mapping and Classical Music Accompaniment - Sriyono, Sriyono (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this research is to evaluate the effect of using mind mapping learning accompanied by classical music on chemistry learning outcomes on hydrocarbon compound material in class X students at Public High School 2 North Bengkulu. Methodology: This research uses an experimental method with a t-test research design, where class X-3 is the control group that follows conventional learning, and class. Data collection instruments consist of pre-test and post-test questions. The analysis used data about learning outcomes using analysis descriptive and inferential. Main Findings: The results of descriptive analysis show that the experimental class that used mind mapping accompanied by classical music had higher learning outcomes compared to the control class that followed conventional learning. The results of inferential analysis using the homogeneity test and normality test stated that the research hypothesis was accepted, indicating that there were significant differences in student learning outcomes between the two groups. The use of mind mapping learning accompanied by classical music can significantly improve student learning outcomes in hydrocarbon compound material compared to conventional learning. Novelty/Originality of this study: The novelty of this research is to determine the effectiveness of applying the mind mapping learning model accompanied by classical music to improve chemistry learning outcomes on hydrocarbon compound material.